RESECTION AND RECONSTRUCTION OF GIANT TOPHUS OF THE FOOT : A CASE REPORT - Rhyan Darma Saputra; Bintang Soetjahjo; Bagus Jati Nugroho; Jiva Yori Anugrah (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: The first metatarsophalangeal joint is the most frequent site of gouty tophi (MTP1). With the incidence of MTP1 joint was 73 %. Treatment aims at control of serum uric acid levels which can cause regression of tophi and surgical excision of very large tophi. A case of a massive tophus at the first metatarsophalangeal joint was documented. Case presentation: AÂ 58-year-old man was diagnosed with and a huge tophus at MTP1,after a five-year history of the goutÂ disease. The patient was referred to our hospital because of a developing mass. On examination of the left foot, there was a solid mass on the dorsal and plantar forefoot that was fixed and had an unclear margin. There was no discomfort on the lump. The 1st metatarsal and proximal phalanges bones were both destroyed on a plain radiograph of the left foot. A laboratory examination shown increased at uric acid level (11.3 mg/dl), increased at sedimentation rate (46 mm/h at first hour), and also increased lactate dehydrogenase (LDH). We performed Excision of tophi and continued with reconstruction and arthrodesis MTP1 & MTP2 using iliac auto bone graft then internally stabilized with Mini T-Plate and K-Wire Conclusion: Patient with giant tophus at first metatarsophalangeal joint can be treated with excision and performed arthrodesis. Keywords: First metatarsophalangeal, giant tophus, arthrodesis